Colonial Terrors in Trabalhar Cansa and as Boas Maneiras by Juliana Rojas-Marcos Dutra: The Negritude as the Stain That Corrodes It All - Hermosilla-Órdenez, E (Oxford University Press, 2025)
Brazilian cinema and television hide or minimize the representation of Afro-descendent people, presenting them as secondary characters. This lack of racial diversity is reproduced in horror cinema, in which white men have a predominant place in films that show their fears. However, Juliana Rojas s and Marcos Dutra s Trabalhar Cansa (2011) and As Boas Maneiras (2017) approach horror as an experience profoundly entrenched within Brazil s colonial past and the modern abuses and the exploits of non-white people. This chapter analyzes the ways these films position horror as an experience closely tied with race, social class, gender identity, and sexuality, as well as the Latin American colonial past. Using Mabel Moraña s work about the monster in Latin America and the Caribbean, and decolonial feminist scholarship by María Lugones and Rita Segato, this chapter reveals how the fears of the women characters in Trabalhar Cansa and As Boas Maneiras highlight different expressions and intensity of the horror between Black and white women. Thus, the films show how the horror is bound in the white, patriarchal, capitalist regime. © Oxford University Press 2025. All rights reserved.